Myogenesis control by SIX transcriptional complexes. (August 2020) - Maire, Pascal; Dos Santos, Matthieu; Madani, Rouba; Sakakibara, Iori; Viaut, Camille; Wurmser, Maud
Abstract: SIX homeoproteins were first described in Drosophila, where they participate in the Pax-Six-Eya-Dach (PSED) network with eyeless, eyes absent and dachsund to drive synergistically eye development through genetic and biochemical interactions. The role of the PSED network and SIX proteins in muscle formation in vertebrates was subsequently identified. Evolutionary conserved interactions with EYA and DACH proteins underlie the activity of SIX transcriptional complexes (STC) both during embryogenesis and in adult myofibers. Six genes are expressed throughout muscle development, in embryonic and adult proliferating myogenic stem cells and in fetal and adult post-mitotic myofibers, where SIX proteins regulate the expression of various categories of genes. In vivo, SIX proteins control many steps of muscle development, acting through feedforward mechanisms: in the embryo for myogenic fate acquisition through the direct control of Myogenic Regulatory Factors; in adult myofibers for their contraction/relaxation and fatigability properties through the control of genes involved in metabolism, sarcomeric organization and calcium homeostasis. Furthermore, during development and in the adult, SIX homeoproteins participate in the genesis and the maintenance of myofibers diversity.